Conventions 101 A Functional Approach to Teaching (And Assessing!) Grammar and Punctuation - Ramsey, Chauna (Open textbook library., 2016)
This is a collection of cumulative units of study for conventional errors common in student writing. It's flexible, functional, and zeroes in problems typically seen in writing of all types, from the eternal “there/they're/their” struggle to correct colon use. Units are organized from most simple to most challenging.